2020
DOI: 10.1097/meg.0000000000001886
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection of gastric neoplastic lesions in Western countries: systematic review and meta-analysis

Abstract: Endoscopic submucosal dissection (ESD) for gastric neoplastic lesions removal is largely performed in Asian countries. Unfortunately, ESD diffusion, particularly for gastric lesion removal, is still limited in Western countries. We performed a systematic review of available data coming from Western centers. The en bloc and the R0 resection rates for all neoplastic lesions, including early gastric cancer (EGC) and dysplasia, were calculated, as well as the curative rate for EGC. Complications and the 1-month mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
(37 reference statements)
0
13
1
Order By: Relevance
“…Our perforation rate was slightly higher than that reported by Oda in a review of 28 Japanese and Korean studies, including > 300 gastric ESD each, which ranged from 1.2%-5.2%, and also higher than the values reported by Zullo et al in a meta-analysis of Western studies with an overall rate of 3.4% (95% confidence interval [CI], 2.5%-4.6%). 27,30 However, as Zullo et al 27 pointed out, the perforation rate was higher in studies with few patients, even reaching 22%. The perforation rate is closely related to the learning curve.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Our perforation rate was slightly higher than that reported by Oda in a review of 28 Japanese and Korean studies, including > 300 gastric ESD each, which ranged from 1.2%-5.2%, and also higher than the values reported by Zullo et al in a meta-analysis of Western studies with an overall rate of 3.4% (95% confidence interval [CI], 2.5%-4.6%). 27,30 However, as Zullo et al 27 pointed out, the perforation rate was higher in studies with few patients, even reaching 22%. The perforation rate is closely related to the learning curve.…”
Section: Discussionmentioning
confidence: 98%
“…[22][23][24][25][26] A systematic review including six Latin American studies, revealed en bloc, R0, and curative overall resection rates of 96%, 84%, and 72%, respectively. 27 To our knowledge, the largest Western series of ESD for EGC has recently been published by Ngamruengphong et al, 28 who reported en bloc, R0, and curative resection rates of 92.2%, 91.8%, and 58.7%, from 347 lesions resected in several hospitals in the United States. An important Latin American study by Arantes et al 13 reported achieving en bloc and R0 resection rates of > 90% and a curative resection rate of 76% in 35 adenomas and 42 EGCs resected by ESD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The rate of post-ESD bleeding is also various (0-15.6%) (12)(13)(14)(15); this rate for patients with antithrombotic agents or anticoagulants is even higher. Takeuchi et al (16) found that post-ESD bleeding in antithrombotic group was 23.3%, significantly higher than 2.0% in the non-antithrombotic group.…”
Section: Definition and Incidencementioning
confidence: 99%